5.9t-9.5=-12.5+4.9t

Simple and best practice solution for 5.9t-9.5=-12.5+4.9t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5.9t-9.5=-12.5+4.9t equation:


Simplifying
5.9t + -9.5 = -12.5 + 4.9t

Reorder the terms:
-9.5 + 5.9t = -12.5 + 4.9t

Solving
-9.5 + 5.9t = -12.5 + 4.9t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-4.9t' to each side of the equation.
-9.5 + 5.9t + -4.9t = -12.5 + 4.9t + -4.9t

Combine like terms: 5.9t + -4.9t = 1t
-9.5 + 1t = -12.5 + 4.9t + -4.9t

Combine like terms: 4.9t + -4.9t = 0.0
-9.5 + 1t = -12.5 + 0.0
-9.5 + 1t = -12.5

Add '9.5' to each side of the equation.
-9.5 + 9.5 + 1t = -12.5 + 9.5

Combine like terms: -9.5 + 9.5 = 0.0
0.0 + 1t = -12.5 + 9.5
1t = -12.5 + 9.5

Combine like terms: -12.5 + 9.5 = -3
1t = -3

Divide each side by '1'.
t = -3

Simplifying
t = -3

See similar equations:

| 5m+7-2m-1= | | 11S^2+S-10=0 | | 17=m+3 | | 4x-2x+5=-7 | | 6y-5y-3=8 | | 25=m+4 | | 8k^2=688 | | 6s=-36 | | x+172+32+x=180 | | 7+z=12 | | -3(x-1)=4(3-2x)+7 | | 6x-7-3x= | | h+31=-22 | | 4x+6y=1080 | | x^2+9=59 | | 9(t+2)=6(t-2) | | 0.9=-8c+0.5+9c+0.2 | | 28=m-5 | | h-2=4 | | -5(6y-6)-y=-2(y-3) | | ln(x-3)-2=8 | | 2+(-5)=x | | 2(x+4)-16=20 | | 1.5y+6= | | 2x+9=x^2 | | m+29=-52 | | x-48=-47 | | 7x-3+11x+3=162 | | 3kx^2-2kx+1=0 | | 3.6=r-2.3 | | -4x+6=2x+18 | | a^2-8=26 |

Equations solver categories